STRUCTURE OF DIATOM PLANKTONIC COMMUNITY IN COASTAL AROUND DUMAI CITY RIAU PROVINCE - Siregar, Eva Desy Yulina; Siregar, Sofyan Husein; ', Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in March 2015 to find out the structure of  diatom community and the distribution of abundance planktonic diatom in coastal around Dumai City. The survey method was applied in four stations with different characteristics, each stasiun consisted three sampling strata. The total of diatomwere 10 genera namely:Eucampia, Leptocylindrus, Guinardia, Rhizosolenia, Melosira, Coscinodiscus, Thalassiothrix, Rhabdonema, Nizschia, and Bacillaria. The most genera that commonly found was Rhizosoleniabecause yhis genera was being able to compete better than other genera. Base on the formulation of diversity index (H'), dominance index (D), and equability index (E), explained that the structure of diatomplanktonic community in all stations were in a state of balance. It  means there was not competition both places and food. The result of ANOVA test gained that the distribution of the diatom abundance was not significantly different among stations.   Key Words: abundance, diatom planktonic, Dumai